Ethnographic Research: Potential of Local Culinary as a Tourist Attraction Object in Simalungun Regency, Indonesia - Indra, Rama; Sibarani, Robert; Revida, Erika; Rujiman (International Journal of Economics and Management, 2024)
The objectives of this research include exploring the potential of local culinary as a tourist attraction in four Destination Tourist Objects (ODTW), namely Haranggaol, BIS, Sibaganding, and Parapat in Simalungun Regency, Indonesia. The interconnection between food and tourism is currently growing. This research is an ethnographic study to support the acceleration of culinary tourism development in Simalungun Regency. Data were collected through observation and ethnographic interviews with 3 informants, namely key informants, main informants, and supporting informants. Using selective observation and contrasting questions, several contrasting dimensions among the residents of a domain can be identified (for example, we will know that the main foods are "dayok nabinatur" and "saksang," while desserts are found in "lapet boras" and "marlakop-lakop," and perhaps many more contrasts between main dishes and desserts). Such contrasting issues are the focus of componential analysis. Categorization of culinary based on local wisdom can be seen from the following elements: 1) culinary naming in Batak language; 2) cultural themes behind culinary presentation; 3) basic food ingredients; 4) local spices/herbs; and 5) the cooking process of local culinary. The potential of local culinary wisdom and culinary tourism based on local wisdom is worthy of development into a new tourist attraction, namely culinary tourism, to attract tourists.